Effect of exercise on glucose variability in healthy subjects: randomized crossover trial - Franciele Ramos Figueira; Daniel Umpierre; Patrícia Martins Bock; Gustavo Waclawovsky; Ana Paula Guerra; Anderson Donelli; Michael Andrades; Karina Rabello Casali; Beatriz D. Schaan (Termedia Publishing House, 2019)
The aim of this study was to evaluate the acute effect of aerobic (AER) and eccentric (ECC) exercise on glucose variability, correlating it with circulating markers of inflammation and oxidative stress in healthy subjects. Sixteen healthy subjects (32 ± 12 years old) wore a continuous glucose monitoring system for three days. Participants randomly performed single AER and ECC exercise sessions. Glucose variability was evaluated by glucose variance (VAR), glucose coefficient of variation (CV%) and glucose standard deviation (SD). Blood samples were collected to evaluate inflammatory and oxidative stress markers. When compared with the preexercise period of 0-6 h, all the indices of glucose variability presented comparable reductions 12-18 h after both exercises (∆AER: VAR= 151.5, ∆CV% = 0.55 and ∆SD = 3.1 and ECC: ∆VAR = 221.2 , ∆CV% = 3.7 and ∆SD = 6.5). Increased interleukin-6 (IL-6) levels after AER (68.5%) and ECC (30.8%) (P